SUSTAINABLE TOURISM DEVELOPMENT – CASE OF THE WOLIN REGION - Brelik, Agnieszka (Acta Scientiarum Polonorum. Oeconomia, 2012)
The aim of the research was to present the most important factors for sustainable tourism development, and analyze the Wolin community’ involvement to the principles of sustainable development. The research assumes that knowledge about sustainable development among residents of Wolin region has a big influence on their involvement in tourism development and environmental protection. Source materials on the opinion of residents were obtained from tests performed in 2010. The study involved 100 residents; the data collection questionnaire method was used. Material collected in conjunction with the source material was prepared in the form of summary tables for the presentation of the issues discussed. For study relationships between the selected features were used the coefficient correlation, V-Cramer’s based on χ2 statistics.